Study on the In Vitro and In Vivo Antioxidant Activity and Potential Mechanism of Polygonum viviparum L. - Zhen Yang; Jingyuan Man; Haoyu Liu; Di Wu; Qiangwen Gu; Hongjuan Zhang; Yu Liu; Dan Shao; Baocheng Hao; Shengyi Wang (Antioxidants)
Oxidative stress refers to the phenomenon in which the redox balance of the body is disrupted in response to stimuli, leading to an excessive accumulation of reactive oxygen species in vivo, which can lead to a variety of diseases. In contrast to artificial antioxidants, whose safety is controversial, natural antioxidants, which are widely available, pharmacologically active, and have little toxic side effects, are expected to be candidates for the treatment of oxidative stress-related diseases. Polygonum viviparum L. (PV) is a natural herbal medicine with antioxidant properties and is used as a traditional medicine in the Tibetan Plateau region. However, there are few studies that have focused on its antioxidant activity and mechanism of action in vitro and in vivo. Therefore, the present study firstly demonstrated that PV could exert good in vitro antioxidant effects by scavenging DPPH radicals and inhibiting the production of hydroxyl radicals through in vitro experiments. Secondly, PV was proven to attenuate the effects of oxidative stress on body weight gain and thymus development by establishing the Senna leaf-induced diarrhea model in rats, as well as to increase the activity of antioxidant enzymes and the content of non-enzymatic antioxidants in the intestinal tract and to enhance the rats’ own antioxidant defenses, to mitigate the oxidative damage caused by diarrhea. Subsequently, the application of the cellular oxidative stress model evidenced that PV could play a protective role against cellular oxidative stress by inhibiting the overaccumulation of ROS in macrophages. Furthermore, the candidate antioxidant targets of PV were analyzed and screened using a comprehensive network pharmacology method, and their expression were then examined at the mRNA level and protein level. Our results suggest that PV may protect against H2O2-induced oxidative damage in macrophages by activating BCL2L1 and inhibiting ESR1, JAK2/STAT3, and MMP2. These findings open new perspectives on the antioxidant mechanism of PV and the prospect of developing it as a novel natural antioxidant drug.